Sosialisasi dan Edukasi Kenakalan Remaja dan Bullying di SMPN Satap 1 Ladongi - Saranani, Milawati (Yayasan Daarul Huda Kruengmane, 2026)
Bullying is an intentional act intended to harm another person physically, verbally, or emotionally. Bullying can occur anywhere, including at school, in the workplace, and online. This study aims to understand bullying, its causes, its effects, and its prevention. This study employed a qualitative research method. The data collection technique used was a literature review. The collected data were then analyzed in three stages: data reduction, data presentation, and conclusion drawing. The results indicate that bullying is caused by several factors, including peer group, family environment, and social status. This behavior also has negative effects, including impaired physical health, mental health problems, and the emergence of new bullies. Bullying behavior needs to be prevented, and solutions formulated, including implementing it wisely by utilizing technological advances, avoiding discriminatory attitudes, instilling compassion, socializing through songs, establishing firm regulations regarding bullying, educating perpetrators, providing protection, and taking firm action.